Urokinase-Type Plasminogen Activator System in Norm and in Life-Threatening Processes (Review) - Elena V. Kugaevskaya; Tatiana A. Gureeva; Olga S. Timoshenko; Nina I. Solovyeva (Общая реаниматология)
The multifunctional urokinase-type plasminogen activator system (uPA-system) includes serine proteinase — uPA or urokinase, its receptor (uPAR) and two inhibitors (PAI-1 and PAI-2). The review discusses the structural features and involvement of the system components in the development of life-threatening processes including carcinogenesis, inflammation, neurogenesis and fibrinolysis, in regulation of which the destruction of extracellular matrix (ECM), cell mobility and signaling inside and outside the cell play a decisive role. uPA triggers the processes by activating the plasminogen and its convertion into plasmin involved in the activation of matrix metalloproteinases (MMPs) in addition to the regulation of fibrinolysis. MMPs can hydrolyze all the major ECM components and therefore play a key role in invasion, metastasis, and cell mobility. MMPs activates a cassette of biologically active regulatory molecules and release them from ECM. uPAR, PAI-1 and PAI-2 are responsible for regulation of the uPA activity. In addition, being a signaling receptor, uPAR along with MMPs lead to the stimulation of a number of signaling pathways that are associated with the regulation of proliferation, apoptosis, adhesion, growth and migration of cells contributing to tumor progression, inflammation, chemotaxis, and angiogenesis. Effective participation of the uPA system components in ECM destruction and regulation of intracellular and extracellular signaling pathways demonstrates that the system significantly contributes to the regulation of various physiological and pathological processes.